ANALISIS KEMISKINAN RUMAH TANGGA BERDASARKAN KARAKTERISTIK SOSIAL EKONOMI DI KABUPATEN ACEH BARAT DAYA - Arif Takdir, Abubakar Hamzah, Mohd. Nur Syechalad. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2013)
Abstract: This study is aimed at finding the level of the poverty line in families according to Sajogyo and statistical analysis based on the characteristics of economic social. In addition, the purpose of this study is to know what factors cause the poverty in Southwest Aceh District. The population of this study was 35.128 heads of families. However, the writer took 100 heads of poor families as the sample of the research. This study employed survey method using questionnaires and interviewing technique to collect data. The influence of expenditure on food and non-food to the sub-systen variable of economic social characteristics (the number of family members, level of education, age, age of children, economic activity, and kinds of job) was tested by using the multi-regresion. Statistical analysis of the family poverty line based on the characteristics of economic social in Southwest Aceh based on the number of family members as the sub-system is IDR 468.406,25; based on the level of education is IDR 800.723,70; and the group of children’s age is IDR 494.567,71, and the average poverty line is 563.890,34.The poverty in Southwest Aceh is caused by two factors, they are theological normative and sociological structure. Keywords: Poverty, Characteristics of Economic Social, Poor Family, Poverty Line. Abstrak: Tujuan penelitian ini adalah untuk mengetahui seberapa besar garis kemiskinan (poverty line) rumah tangga dan untk mengetahui faktor-faktor penyebab kemiskinan di Kabupaten Aceh Barat Daya.Populasi dalam penelitian ini adalah 35.128 kepala keluarga dengan sampel 100 KK miskin. Penelitian ini menggunakan metode survey dengan teknik pengumpulan data berupa angket dan wawancara. Pengaruh pengeluaran makanan dan non makanan terhadap variabel subsisten di uji dengan menggunakan regresi berganda. Analisis statistik garis kemiskinan rumah tangga berdasarkan karakteristik sosial ekonomi di Kabupaten Aceh Barat Daya, dilihat dari jumlah anggota keluarga/tanggungan sebagai subsisten sebesar Rp 468.406,25, tingkat pendidikan sebagai subsisten adalah sebesar Rp 800.723,70 dan kelompok umur anak sebesar Rp 494.567,71 serta rata-rata garis kemiskinan adalah sebesar Rp 563.890,34. Kemiskinan di Aceh Barat Dayadisebabkan oleh dua faktor, yaitu normatif-teologis dan struktural-sosiologis. Kata Kunci: Kemiskinan, Karakteristik Sosial Ekonomi, Rumah Tangga Miskin, Garis Kemiskinan.